Lack of Direct Effects of Agrochemicals on Zoonotic Pathogens and Fecal Indicator Bacteria - Staley, Zachery R. (American Society for Microbiology, 2012)
Agrochemicals, fecal indicator bacteria (FIB), and pathogens frequently contaminate water simultaneously. No significant direct effects of fertilizer, atrazine, malathion, and chlorothalonil on the survival of Escherichia coli, Enterococcus faecalis, Salmonella enterica, human polyomaviruses, and adenovirus were detected, supporting the assertion that previously observed effects of agrochemicals on FIB were indirect.